An e-module analysis for problem-based learning with a focus on developing students' critical thinking skills (Asian Journal of Educational Technology, 2022)
21st century education is expected to produce competent human resources in 21st century skills. Teachers must integrate information technology facilities to help participants learn with teaching materials, methods, and technology-based teaching media. This study aimed to describe PBL-based E-Modules to empower critical thinking skills in elementary school learning at SDN 01 Sangkaran Bhakti. This research is a descriptive qualitative research. Data and data sources were collected from interviews and questionnaires for 6 teachers and 15 students, then the data were analyzed by interactive analysis. The results showed that PBL-based E-Modules can empower critical thinking skills in elementary school learning as a 21st century digital media innovation. E-modules as learning media are combined with text, narration, video, practice questions and integration with learning models. PBL-based E-Modules as an effective solution for 21st century learning are in accordance with the character of the material and learning styles of 21st century students as digital natives